Psikologi keluarga: Membangun keharmonisan dan keseimbangan dalam keluarga - Firmansyah, Aditya (Maliki Interdisciplinary Journal, 2025)
Islamic family psychology is a science that studies the soul or mentality, in the form of behavior and mental processes in the family, based on Islamic teachings. This article discusses the understanding, function and benefits of Islamic family psychology in building harmony and balance in the family. By using references from several sources, this article explains that Islamic family psychology can help develop individual and family potential, as well as strategies for overcoming problems and solving problems. Apart from that, this article also discusses the impact of child psychology on household relationships and strategies for building a harmonious family through good communication, quality time and wise supervision. Thus, Islamic family psychology can be an effective tool in creating a family environment that supports children's growth and development and strengthens family bonds.